Assessment of Prescription Pattern at Outpatient Department in a Tertiary Care Hospital at Central Maharashtra, India - Shruti Chandra; Deepak Bhosle; Amol Ubale (Technological Innovation in Pharmaceutical Research Vol. 11, 2021)
Introduction: Drug utilization studies are powerful tools to ascertain the role of drug in society. They create a sound socio-medical and health economic basis for healthcare decision making. DUS are conducted to facilitate the rational use of drugs in populations. The indicators of prescription in practice measure the performances of health care provider in several key dimensions related to appropriate use of drug. Therefore, the present study was undertaken to analyze the prescription written by doctors in a Tertiary Care teaching Hospital. Materials and Methods: Present study was a cross sectional, prospective and observational study. The study was conducted in MGM Medical College & Research centre, Aurangabad from July 2018 to March 2019 for duration of 9 months. Data was obtained from 850 prescriptions. Data was analysed as per WHO prescribing indicators. Results: Total 850 prescriptions were analysed, including 490 (57.6%) males and 360 (42.3%) females. The maximum numbers of prescriptions were from the age group of 18-40 (53.6%) years of age. Average number of drugs in the present study was found to be (3.1). Percentage of drugs prescribed by generic name is 16.0%. Percentage of encounters with an antibiotic prescribed was 59.1%. Percentage of encounters with an injection prescribed was 4.9%. Percentage of drugs prescribed from essential drugs list was 68.4%. Conclusion: There is need of improving the prescribing pattern by keeping the number of medicines as low as possible, prescribing medicines by generic names, using medicines appropriately after selecting and consciously keeping the cost of therapy low. Health professionals have a responsibility to ensure that the right drug is prescribed, dispensed and taken.